Residential acoustic performance: an applicability study - Silva, Ananias Freire da (2019)
The civil construction industry has in recent years presented profound transformations, a fact that imposes on the professional constructor new paradigms of labor practice. Within this context, the standardization of technical procedures in the world has been evolving at a rate proportional to these changes. As an example, NBR 15.575, Brazilian standard that determines performance standards in civil construction fully entered into force in 2013 and with it brought minimum requirements to the acoustic performance in residential buildings. This little discussed theme, often ignored by the productive chain of civil construction, has therefore become more of a challenge to be put into practice in modern constructions. This work, in turn, is a bibliographic study of acoustic performance, focused on the applicability of these procedures. The objective of this work is to analyze the feasibility of using acoustic insulation techniques and materials in residential buildings. Divided methodologically into four parts, the first part dealt with the concept of performance and the historical path covered by NBR 15.575. In the second part an academic study of acoustic was traced, emphasizing the physical aspects of the nature of the sound waves. In the third section there is an in-depth study of the constructive aspects required for a building recommended in NBR 15.575. Finally, in the fourth one, the use of materials and techniques of technological innovation directed to residential acoustic treatment was exemplified, and its objective is to analyze the feasibility in the use of techniques and acoustic insulation materials in residential constructions. The results pointed out that this standard has become a milestone and fully meets its objective. An important fact observed in this research is the clear accountability of the agents involved in the process of construction, sale and acquisition of a residence, leaving each professional, and also user, aware of their duties beforehand.